Effect of Cryopreserved Cord Blood on Structure of Immunocompetent and Other Vital Organs at Acute Pyoperitonitis - Goltsev, K. A.; Volina, V. V.; Kozhina, O. Yu.; Ostankov, M. V. (Problems of Cryobiology and Cryomedicine, 2011)
The experimental research of the effect of cryopreserved human cord blood (cHCB) introduction on the recovery of structure of immuno-competent and other vital organs of rats with acute pyoperitonitis (APP) was performed. It was shown the activation of regenerative processes under effect of cHCB in immune system organs as well as other ones (liver, kidneys, intestine and lungs) exposed to pathological changes at peritonitis development. The obtained results provide the reasons for probable cHCB administration as an immunomodulating therapy at development of acute pyoperitonitis in clinical practice.